POLA PERJALANAN WISATA KOTA PEKANBARU - Diorsa Yamagi; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Pekanbaru City has several interesting and unique tourist objects to visit. Therefore, there is a need for a pattern of tourist trips that are arranged to attract tourists visiting the city of Pekanbaru. This research was conducted to uncover tourist objects in the city of Pekanbaru and arrange them in the form of tourist travel patterns.The purpose of this study is to identify the objects and tourism potential in the city of Pekanbaru as well as uncover the cluster of travel patterns and recommend patterns of tourist travel in the city of Pekanbaru. This research uses descriptive qualitative method with data collection techniques, namely theory, observation, interview and documentation.The results of this study are to uncover the tourism objects and potential in the city of Pekanbaru, and recommend patterns of tourism in the city of Pekanbaru.Keywords: Travel Pattern, Tourism, Pekanbaru City